2017
DOI: 10.1177/2333392817734206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Diabetes Care for Patients With Serious Mental Illness Using the Chronic Care Model

Abstract: People with serious mental illness (SMI) have a higher incidence of type 2 diabetes mellitus (T2DM) and shorter life span due to medical health problems. The chronic care model (CCM) has been used to improve care of patients with T2DM. One clinical organization that provided primary care to patients with SMI had excellent diabetes outcomes but did not have information on how they achieved those outcomes. Thus, we conducted a pilot study chart review for 30 patients with T2DM and SMI to determine how well the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…71 It was suggested that type 2 diabetes care could be improved if there was clarity in the division of labour between professional groups. 84 For example, the need to improve communication with other health professionals was identified by one study in this review, 93 suggesting a recognition of the importance of this skill but a need for improved ability. These factors were also identified within this synthesis with a variable, and at times contradictory belief, about professional responsibility identified.…”
Section: And Identitymentioning
confidence: 95%
See 3 more Smart Citations
“…71 It was suggested that type 2 diabetes care could be improved if there was clarity in the division of labour between professional groups. 84 For example, the need to improve communication with other health professionals was identified by one study in this review, 93 suggesting a recognition of the importance of this skill but a need for improved ability. These factors were also identified within this synthesis with a variable, and at times contradictory belief, about professional responsibility identified.…”
Section: And Identitymentioning
confidence: 95%
“…For example, mental health professionals' difficulties in accessing timely information, such as scheduled type 2 diabetes care appointments, impacted their ability to motivate service users and support their clinic attendance. Both mental and physical health professionals cited that there were challenges in providing type 2 diabetes care owing to pressures resulting from reduced staff levels, 73,74,75,76,78,79,81,82,83,84 workload, 73,76,79 and a perceived lack of time; 37,73,74,75,78,80,81,82,85,86 although in one study mental health nurses and support workers felt they had sufficient time, and more so than general practitioners. 38 The identified pressures were compounded by the complex needs of individuals with both type 2 diabetes and SMI, who were deemed "undesirable" due to the "large amount of resources required to treat them such as longer medical visits to explain treatment".…”
Section: Context and Resourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Self-management is an important aspect of T2D treatment, and can be enhanced with the implementation of a personalized care plan. 2 Personalized care plans draw upon the "chronic care model," 3,4 which regards the patients as experts in their own disease, and actively involves them in their own health care strategy. A care plan requires motivational discussion between care providers and the patient.…”
Section: Introductionmentioning
confidence: 99%